TOWARD CREATIVITY AND SPEAKING ABILITY OF EFL STUDENTS: A MIXED-METHOD STUDY - Debiga Fikky Abdullah; Diah Kristina; Sumardi Sumardi (LLT Journal: A Journal on Language and Language Teaching, 2020)
The present study employed a mixed-method approach to investigate creativity and speaking ability of EFL learners towards its relationship and other essential factors. Indonesian EFL students of the 5th semester taken the course of Academic Speaking in a private university (n=30) who were selected randomly responded Creative Personality Scale (CPS) and Self-Rating of Creativity. For the former, they described themselves by checking off 18 positively scored and 12 negatively scored items which were given a value of +1 and a value of -1, respectively. The latter was assessed by using eight items from the creativity scale. The 7-point Likert-type scales (1=strongly disagree, 7=strongly agree) were made to respond these items. Following this, the students' monologues based on five themes were scored using the IELTS Speaking Test Descriptor. The data were analyzed using Spearman rank-order correlation coefficient, pattern matching, and explanation building. The finding shows a significant correlation between EFL learners' creativity and their speaking ability (? = .961). The students also faced up to the cultural constraints in advancing their creativity. This study should, therefore, be of value to practitioners wishing to provide EFL students with appropriate materials that are addressed to enhance their speaking ability.